The New Collective Behavior in Digital Society: Connection, Contagion, Control - Lee, Raymond L.M. (Lexington Books, 2023)
In The New Collective Behavior in Digital Society: Connection, Contagion, Control, Raymond L.M. Lee offers an updated view on the sociology of crowds. While the era of crowds that Le Bon famously wrote about more than a century ago reflected the social and political crises of his time, in the twenty-first century we encounter a completely new scenario with crowds forming online or morphing into swarms in digital space. Lee confronts large gatherings that are only virtually present and investigates collective behaviors that are not always palpable and visceral. This is the age of digital dominance where the collective becomes reduced to ones and zeros to become more vulnerable to the social and political interventions of our time. This book attempts to discern and dissect those interventions, focusing on the power of virality that sustains networks, assemblages, and platforms to generate new collective behaviors in an era of smartphones, surveillance, and pandemics that were never imagined in Le Bon’s time.